On the Turnover of Business Firms and Business Managers - Holmes, Thomas J.; Schmitz, James A. (Journal of Political Economy, 1995)
This paper develops a model of small business failure and sale that is motivated by recent evidence concerning how the failure and sale of small businesses vary with the age of the business and the tenure of the manager. This evidence motivates two key features of the model: a match between the manager and the business, and characteristics of businesses that survive beyond the current match. The parameters of the model are estimated, and the properties of this parametric model are studied. This analysis results in a simple characterization of the workings of the small business sector.